DAMPAK LIKUIDITAS, RISIKO KREDIT DAN DANA PIHAK KETIGA TERHADAP PROFITABILITAS PADA BANK PERKREDITAN RAKYAT TANGERANG: indonesia - ade onny siagian (Politeknik Ubaya, 2021)
The purpose of this study is to find the profitability of a financial ratio that measures industry expertise in using its assets to generate profits. Continuing to be large, profitability shows that the industry's performance continues to be good, because the rate of return continues to be large. There are several variables that affect the profitability of a bank, namely liquidity, credit risk and third party funds. A bank is an institution that acts as a financial intermediary between parties that have excess funds and those who lack funds. The performance of a bank can be assessed through the financial statements presented by Bank Indonesia by carrying out an analysis using financial ratios. This research was conducted on the financial statements of BPR Tangerang Regency for the period 2016-2019. This research has the theme